2016
DOI: 10.1016/j.apsoil.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of precipitation manipulation and nitrogen addition on soil properties in California grassland and shrubland

Abstract: Soil microbial communities and pools of carbon (C) and nitrogen (N) play an important role in ecosystem responses to precipitation variability and N deposition. In southern California, ecosystem vulnerability to these environmental change drivers may differ for grassland versus shrubland vegetation types. We hypothesized that 1) these vegetation types would differ in their responses to precipitation and N manipulation; 2) reduced precipitation ("drought treatment") would have a negative effect on soil microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…While soil microbial community and enzyme activity could have contributed to changes in soil C and N processes [ 51 53 ], which should be considered in further studies examining understory vegetation effects on soil C and N process. In addition, this study was conducted in areas with similar erosion levels before the colonization of both studied understory vegetation types.…”
Section: Discussionmentioning
confidence: 99%
“…While soil microbial community and enzyme activity could have contributed to changes in soil C and N processes [ 51 53 ], which should be considered in further studies examining understory vegetation effects on soil C and N process. In addition, this study was conducted in areas with similar erosion levels before the colonization of both studied understory vegetation types.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in this Mediterranean grassland ecosystem, soil moisture, which is affected by season, depth, heating, and plants, plays a dominant role in mediating the effect of those factors on root litter decomposition, which after two seasons did not differ by depth or by treatment. Therefore, it will be important to complement this study with others that manipulate soil moisture (e.g., Suttle et al 2007;Khalili et al 2016) to better understand how decomposition of plant litter and soil organic matter will respond and feedback to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk is a serious concern in arid shrublands and grasslands in southern California with a Mediterranean climate, where the probability of fire increases exponentially above a threshold of N loading [154]. The combined effects of drought and N deposition increases the pools of soil labile N, suggesting a build-up of available N, with unpredictable effects on soil trophic webs, plant-community diversity and C-storage capacity [155]. The potential increase in litterfall production together with the increasing frequency of fire in the Mediterranean area of southern California can favor the spread of shrubs able to sprout over shrubs that depend on seed germination [156].…”
Section: Forests Versus Shrublands and Grasslandsmentioning
confidence: 99%